7 & 7 Synch and 7-day progesterone- based protocols for estrus synchronization prior fixedtime artificial insemination in multiparous beef sucked cows - Ferre, Luis Bernardo; Jaeschke, Julian; Gatti, Juliana; Baladón, Gerardo; Bellocq, Ezequiel; Fernández, Gustavo; Thomas, Jordan M. (ICAR, 2022)
Poster